When Cooperation Becomes Ubiquitously Digital : A Review of Collaborative Society (Dariusz Jemielniak, Aleksandra Przegalinska, Collaborative Society, The MIT Press 2020) - Zygmuntowski, Jan (Zagadnienia Naukoznawstwa, 2022)
In recent years, the majority of studies on new technology-related phenomena have focused either on proving the benefits of innovative solutions or on criticizing social costs. The path chosen in the reviewed book Collaborative Society by Dariusz Jemielniak and Aleksandra Przegalinska is to capture a wider cultural shift that is taking place because ICT (Information and Communication Technology) tools allow people to take advantage of their willingness to cooperate. The key thesis is that the collaborative society goes far beyond the sharing economy – or economy in general. New means of digital communication, remix culture and citizen science prove that this shift is transforming social relations and our mutual relations. The authors search for the manifestations of a collaborative society in joint online production and consumption, cooperation of social activists and hacktivism, social production of knowledge, gadgets encouraging cooperation and subversive connection in digital spaces. The future of cooperation is a story about the tension between the new, communal mode of production and its distortion by capitalism. The book is a good summary of the research area and an introduction for anyone looking to explore this topic or participate in a collaborative society.